Design of home control system prototype using Arduino uno microcontroller based on smartphone (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2023)
Many facilities are designed automatically to help and facilitate human activities in managing the environment or room of the house in order to increase comfort, efficiency, and tighter security. And, if you want to avoid crime such as theft, robbery, and other criminal acts, as well as other calamities such as fire that can not be predicted by us. Based on these problems, of course it needs a control system that is able to help and facilitate human activities in managing and managing a house without having to do it manually or can be called an automatic home. Such as an automatic door lock tool, turn on the electric socket, turn on the lights automatically and the home security system and can also detect fires automatically. Which can be combined with mobile or smartphone technology. This information system development design uses the Object Oreinted approach and the Prototyping development method. Meanwhile, the application of the control system prototype uses an arduino uno microcontroller that uses the C programming language and App Inventor. From the results of testing this prototype is expected to help solve the problems faced by homes today.